The regulatory process and practical significance of non-coding RNA in the dissemination of prostate cancer to the skeletal system - Sang, Hui; Li, Luxi; Zhao, Qiang; Liu, Yulin; Hu, Jinbo; Niu, Peng; Hao, Zhenming; Chai, Keqiang (Frontiers in Oncology, 2024)
Prostate cancer is a major contributor to male cancer-related mortality globally. It has a particular affinity for the skeletal system with metastasis to bones seriously impacting prognosis. The identification of prostate cancer biomarkers can significantly enhance diagnosis and patient monitoring. Research has found that cancer and metastases exhibit abnormal expression of numerous non-coding RNA. Some of these RNA facilitate prostate cancer bone metastasis by activating downstream signaling pathways, while others inhibit this process. Elucidating the functional processes of non-coding RNA in prostate cancer bone metastasis will likely lead to innovative treatment strategies for this malignant condition. In this review, the mechanistic role of the various RNA in prostate cancer is examined. Our goal is to provide a new avenue of approach to the diagnosis and treatment of bone metastasis in this cancer.